Comparing political participation profiles in four Western European countries - Rojon, Sebastien; Pankowska, Paulina K.; Vittori, Davide; Paulis, Emilien (Wiley-Blackwell Publishing Ltd, 2025)
Most studies of political participation have either focused on specific political behaviours or combined several behaviours into additive scales of institutional versus non-institutional participation. Through a multi-group latent class analysis of participation in 15 different political actions, conducted among citizens from four Western European countries, we identified five empirically grounded participant types that differ in their political engagement, socio-demographic characteristics and political attitudes: ‘voter specialists’, ‘expressive voters’, ‘online participants’, ‘all-round activists’ and ‘inactives’. While the same participant types were identified in all four countries, the proportion of citizens assigned to each type varies across countries. Our results challenge the claim that some citizens specialize in protest politics at the expense of electoral politics. Furthermore, our typological approach challenges previous findings on the individual characteristics associated with political (in)action.
Keywords: latent class analysis; political disengagement; political participation; protesting; voting; Taverne; Sociology and Political Science